Optimal Capacitor Placement in Power Distribution System - Dakuri Venkata, Raghavendra (Technium Romanian Journal of Applied Sciences and Technology, 2022)
Optimal Capacitor Placement (OCP) determines the locations, the size and the control settings of these capacitors during each load level of a three-phase distribution system. That will reduce peak power and energy losses and minimise the investment costs and installation of the capacitor banks.  The optimal solution is obtained by testing various combinations of capacitor banks and candidate nodes and the distribution system and calculating the resultant savings.  The capacitor placement problem is a combinational optimisation problem having an objective function composed of energy losses and capacitor bank installation costs subject to the load constraints, network constraints and operational constraints at different load levels.  OCP seeks to maximise the net savings resulting from the reduction in power and energy losses less the total costs of capacitors.  An Artificial Intelligence (A.I.) based Genetic Algorithm (G.A.) has been used to solve the OCP problem.  The proposed method allows the modelling of loads of different power factors for other portions of the power distribution system.  The solution algorithm has been implemented and tested on a ten bus power distribution system, and the simulation results of the proposed algorithm are well executed.